2021
DOI: 10.3390/nu13114108
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Sodium Content of Foods Sold in Four Latin American Countries: 2015 to 2018

Abstract: In 2015, the Pan American Health Organization (PAHO) published sodium targets for packaged foods, which included two distinct levels: one “regional” and one “lower” target. Changes to the sodium content of the food supply in Latin American Countries (LAC) has not been evaluated. A repeated cross-sectional study used food label data from 2015 (n = 3859) and 2018 (n = 5312) to determine changes in the proportion of packaged foods meeting the PAHO sodium targets and the distribution in the sodium content of foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Mean sodium content was assessed (mg/100 g) for commonly consumed sources of sodium, with the results being compared to 2015 PAHO regional targets. The latter analysis found that Paraguay had 87.9% of food products meeting regional sodium targets, followed by Argentina (87.0%), Peru (85.5%), Costa Rica (83.9%) [ 39 ]. In a separate analysis, it was found that 81.2% of Brazil’s food products met the regional sodium targets [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean sodium content was assessed (mg/100 g) for commonly consumed sources of sodium, with the results being compared to 2015 PAHO regional targets. The latter analysis found that Paraguay had 87.9% of food products meeting regional sodium targets, followed by Argentina (87.0%), Peru (85.5%), Costa Rica (83.9%) [ 39 ]. In a separate analysis, it was found that 81.2% of Brazil’s food products met the regional sodium targets [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings also demonstrated high variability in the sodium content of foods within single food categories, suggesting high potential for reformulation of higher sodium products within a food category. This finding, along with the observed high proportion of products already meeting the regional sodium targets, highlighted the need for more stringent regional sodium reduction targets, to accelerate sodium intakes in LAC [ 39 , 40 , 41 , 42 ]. On completion of the IDRC grant, FLIP-LAC was scaled up and made broadly accessible across LAC through another funding source, and results were used to update PAHO regional targets.…”
Section: Resultsmentioning
confidence: 99%
“…Processed foods largely contribute to the sodium intake of people [ 12 , 57 , 58 , 59 ]. Specifically, prepared and prepackaged foods provide about 75% of dietary sodium intake [ 12 , 60 ].…”
Section: Modulation Of Salt Taste Of Food According To Consumer Prefe...mentioning
confidence: 99%
“…The regional target level was the maximum level (mg/100g) or upper limit, whereas food manufacturers were encouraged to reach the lower target level that is reflective of the average level in reference countries 8 . A later study published in 2021 showed that compliance with regional targets increased from 83% to 89% from 2015-2016 to 2017-2018 among four Latin American countries 10 . Therefore, PAHO updated the targets in 2021 to set stronger regional sodium reduction targets for 2022 and 2025 (2022 and 2025 PAHO targets) which are similar to the 2015 PAHO lower targets, and it further categorized foods into 16 main categories and 75 subcategories 11,12 .…”
Section: Introductionmentioning
confidence: 98%